Google Classroom: A Learning Media In Increasing Students' Motivation - M Daud Batubara; Zohri Hamdani; Mark Philip Paderan (Indonesian Journal of Learning Education and Counseling, 2021)
The objective of this study is to know the effect google classroom as learning platform in increasing students’ learning motivation in non-formal education subject of students’ Early Childhood Education programs during the first semester STAIN Mandailing Natal 2020/2021. This study is an experimental research with descriptive analysis. The population of this study was 128 students and there are 25 students as respondents in the cluster class. Pre-test and Post-test were used as techniques in collecting data. To analyze the data, the researcehrs used SPSS 16. The result of this study showed that the mean of pre-test was 47.692 and Post-test was 76.154 which can be concluded that there is an increase in the students’ learning motivation in experimental group using Google Classroom